Public knowledge about smoking as a triggering factor for oral cavity cancer - Arief Siddik Taufan; Shelly Lelyana; Dicha Yuliadewi; Leonardo Jaya Setiadi Tanumiharja (Institute of Computer Science (IOCS), 2026)
Smoking habits in Indonesia are still very high. Approximately 80-90% of oral cancers are caused by smoking, cigars, pipes, and chewing gum. Ignorance of the negative impacts of smoking is considered to be the root of this contradictory situation. The purpose of this study was to determine how the knowledge of rural communities about smoking as a cause of oral cancer has changed. This study aimed to determine how the knowledge of rural communities about smoking as a triggering factor for oral cancer. This study was descriptive and observational with a cross-sectional design. Respondents totaling 171 residents of Margaluyu Village, Pangalengan District, Bandung Regency were selected based on inclusion and exclusion criteria. Data were collected using questionnaires completed during the study and processed using SPSS. The study showed that the majority of residents had low knowledge about smoking as a triggering factor for oral cancer. This can be seen from 92.4% of respondents having a score below 55%, 6.4% of respondents having a sufficient score of 56% - 74%, and 1.2% of respondents having a score above 75%. This study concludes that in Margaluyu Village, Pangalengan District, Bandung Regency, public knowledge about cigarettes as a cause of oral cancer is generally still low.